Improving the survival under gastric conditions of a potential multistrain probiotic produced in co-culture - Marcelo Fernando Valle-Vargas; Yesica Vanesa Rojas-Muñoz; Ruth Yolanda Ruiz-Pardo; Luisa Villamil-Díaz; María Ximena Quintanilla-Carvajal (AMB Express)
Abstract Process and culture medium composition in bioreactor could be optimized in order to find the best conditions that improve survival of probiotic microorganism under exposure to gastric conditions such low pH and bile salts. Therefore, this study aimed to optimize agitation, yeast extract, and di-sodium phosphate (Na2HPO4) concentration to improve the survival under gastric conditions of a multistrain consortium produced in a laboratory bioreactor. Viability, survival low pH (3.00), bile salt tolerance, and antagonistic activity against the pathogen Streptococcus agalactiae were evaluated. As the main result, a high concentration of di-sodium phosphate (2.63% w/v) increased the viability of L. lactis A12 (9.05 to 9.46 Log10 CFU/mL) and Priestia species (0.00 to 6.88 Log10 CFU/mL), survival to pH 3.00 (60 to 93%), survival of bile salts (58– 93%) antagonistic activity (8.74 to 15.56 mm), and final pH of culture medium (4.34 to 6.95). Optimal conditions that improved probiotics characteristics were 150 RPM, 0.83% w/v yeast extract, and 2.63% w/v Na2HPO4. Co-culture of L. lactis A12 with Priestia species improved significantly (p < 0.05) the antagonistic activity (10.41 mm) against S. agalactiae compared to mono-culture (7.70 mm). Our results suggested that was possible to produce a potential multistrain preparation in a lab bioreactor with high viability of L. lactis A12 (9.33 Log10 CFU/mL), high survival to gastric conditions (> 85%), and with antagonistic activity against fish pathogen. This preparation could be used as a feed additive intended for fish nutrition.